Parent participation in physical and psychological cares for their hospitalized children:Viewpoint of healthcare staff - jafarbegloo, smat; mehran, nahid; ahmari tehran, hoda; abedini, zahra; raeesi, marzieh (Advances in Nursing & Midwifery, 2012)
Abstrct Background and Aim: Children healthcare is one of the most important aims of family-centered cares that cause children and family health promotion. Positive attitude of healthcare staff is essential to have parent effective participation in hospitalized children cares. This study was done to evaluate children hospital staff attitude, toward parent participation in physical and psychological cares for their hospitalized children. Methods: This descriptive study was performed on 100 medical staff of Qom children hospital and samples were chosen by convenience sampling method. Data were collected by using questionnaires, including two parts: population specifications and parent participation in hospitalized children cares. Structured questionnaire was designed using a Likert scale with 5 categories ranging from, “completely agreement” to “completely disagreement”.Validity of scale was determined by content validity, and inner correlation method of Cronbach’s alpha (R= 0.82) was used for reliability of scale. Data were analyzed by SPSS software. Results: Scores average and scale deviation (SD) of hospital staff attitude was 94.67±10.96 that is categorized in neutral group. There were no significant relationship between attitude score with age, gender, marital status and education stand. Conclusion: positive attitude of healthcare staff is essential to have family effective participation in hospitalized children cares; so with continuing education courses and health care reform guidelines on children and hospital staff should take part in continuous training programs. Keywords: Attitude, Parent participation, Family-centered care, Hospitalized child.